1992
DOI: 10.1177/030098589202900204
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of Ferritin by Follicle-associated Epithelium in the Colon of Calves

Abstract: Abstract. Uptake of macromolecules (e.g., ferritin) by M cells in follicle-associated epithelium in small and large intestine was investigated in three healthy, conventionally raised, 2-to 3-week-old, female Holstein Frisian calves. A 2.5% solution of ferritin was injected into the ligated loops in mid-jejunum, in terminal ileum, in the ascending colon adjacent to the ileocecal junction, and in the proximal loop of the ascending colon containing gut-associated lymphoid tissue. After exposure times that ranged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 30 publications
(2 reference statements)
1
8
0
Order By: Relevance
“…Preferential uptake of ferritin was shown for M cells in all sites of GALT confirming the function of M cells in GALT [65,71,85]. There are regional differences in the efficiency of M cells to internalize material.…”
Section: Morphology and Function Of The Lymphoepitheliumsupporting
confidence: 64%
See 1 more Smart Citation
“…Preferential uptake of ferritin was shown for M cells in all sites of GALT confirming the function of M cells in GALT [65,71,85]. There are regional differences in the efficiency of M cells to internalize material.…”
Section: Morphology and Function Of The Lymphoepitheliumsupporting
confidence: 64%
“…There are regional differences in the efficiency of M cells to internalize material. Less ferritin was found in the M cells of the large compared to the small intestine and less in LGC compared to lymphoid nodules in the lamina propria [85]. Latex beads and parapox virus are internalized by M cells in the IPP, but not in JPP [65].…”
Section: Morphology and Function Of The Lymphoepitheliummentioning
confidence: 89%
“…Lymphoglandular complexes have been well described in the large intestine of many species, including mice (Owen et al 1991), dogs (Atkins and Schofield 1972), cattle (Liebler et al 1988a, b;Paar et al 1992), sheep (Aleksandersen etal. 1991), pigs (Morfitt and Pohlenz 1989), and human beings (Scott 1982;O'Leary and Sweeney 1986).…”
Section: Discussionmentioning
confidence: 99%
“…Non-lymphoid compartments involve the lamina propria of villi and crypts. PPs are involved in particle uptake and transport into the body fluids and other sites Hussain et al 2001;Paar et al 1992;Smyth et al 2008) and are therefore actively involved in the uptake and transport of infectious agents (Konold et al 2008;Momotani et al 1988;Sigur-Dardottir et al 2001;Jeffrey et al 2006). However, the route, mechanism, and extent of the particle uptake are not yet clear in cattle.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the murine model has also revealed that particle uptake is size-and time-dependent (Doyle-McCullough et al 2007;Hodges et al 1995;Smyth et al 2008). Although a few studies on particle uptake and transport have been preformed on a bovine model (Landsverk 1987;Landsverk 1988;Momotani et al 1988;Paar et al 1992), they have not provided an accurate quantification of intestinal uptake efficiency.…”
Section: Introductionmentioning
confidence: 99%